Calcitriol tablets with hybrid lipid-based solid dispersions with enhanced stability and content uniformity. (8th August 2020) - Yue, Xiao; Cui, Yingtong; Yuan, Ting; Huang, Zhengwei; Huang, Ying; Zhang, Xuejuan; Wang, Chen; Wang, Guanlin; Liang, Ruifeng; Liu, Chunxia; Pan, Xin; Wu, Chuanbin
Abstract: Calcitriol, as the biologically active form of vitamin D3, is essential for patients with renal osteopathy. The solubilization, stabilization, and content uniformity are key issues in its formulation development. In our previous study, the incomplete release of calcitriol was solved by using the hybrid lipid-based solid dispersion (SD) for calcitriol. However, good stability and content uniformity are still urgently needed. In this study, solid lipid with antioxidant properties and liquid lipid compatible with calcitriol were employed as hybrid lipid carrier (HLC) to establish a solid dispersion. Moreover, the content uniformity of tablets with hybrid lipid carrier based SDs (HLCTs) was further guaranteed due to the multi-dispersion of calcitriol in HLC, solidification, and blank granules. Additionally, the compression of the blank granules was adjusted by the water content. The mixing method of calcitriol-containing and blank granules was also optimized. The obtained HLCTs were evaluated for hardness, disintegration time, in vitro drug dissolution, content uniformity, and stability. Satisfactory HLCTs were developed successfully in this study with superior content uniformity and better stability than the commercial soft capsule (Rocaltrol®). It was proved to be a promising formulation for drugs with poor water-solubility, instability to oxygen and heat, and dose-related toxicity.